Effect of Resistance Exercise on Arterial Stiffness during the Follicular and Luteal Phases of the Menstrual Cycle - Okamoto, Takanobu; Kobayashi, Ryota; Sakamaki-Sunaga, Mikako (International Journal of Sports Medicine, 2017)
Acute high-intensity resistance exercise increases arterial stiffness. Changes in blood concentrations of estrogen and progesterone associated with the menstrual cycle affect the degree of arterial stiffness. Therefore, high-intensity resistance exercise may affect arterial stiffness differently depending on the phase of the menstrual cycle. The purpose of this study was to investigate the effects of different phases of the menstrual cycle on arterial stiffness after one session of resistance exercise. The participants were 9 eumenorrheic females (21.3±0.8 years). All participants performed 5 sets of 5 repetitions using 80% of the one repetition maximum (1RM) bench press and 5 sets of 10 repetitions using 70% of the 1RM biceps curl during both the follicular and luteal phases. Brachial-ankle pulse wave velocity (baPWV), blood pressure, and heart rate were measured before (baseline) and at 30 and 60 min after completing the resistance exercises. During the follicular phase, baPWV was significantly increased at 30 and 60 min after the resistance exercise compared with baseline (P<0.05), whereas during the luteal phase, no significant differences were observed after the resistance exercise. These results suggest that high-intensity resistance exercise affects arterial stiffness differently depending on the phase of the menstrual cycle.
Keywords: menstrual cycle; estrogen; progesterone; pulse wave velocity